2017
DOI: 10.1159/000453442
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of a New Synthetic Vitamin E-Bonded Membrane on the Hypo-Responsiveness to the Erythropoietin Therapy in Hemodialysis Patients: A Multicenter Study

Abstract: Background: Oxidative stress has been related to hypo-response to erythropoiesis-stimulating agents (ESAs) in hemodialysis (HD) patients. The aim of this study was to verify whether vitamin E (ViE) on a synthetic polysulfone dialyzer can improve ESA responsiveness. Methods: This controlled, multicenter study involved 93 HD patients on stable ESA therapy, who were randomized to either ViE-coated polysulfone dialyzer or to a low-flux synthetic dialyzer. The primary outcome measure was the change in ESA resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Significantly lower concentration of oxidative stress parameters is achieved on-line by hemodiafiltration with a vitamin E coated membrane in continuity over a 3-6 months period relative to standard hemodialysis with a low-flux membrane without vitamin E. The results of clinical trials suggest that healing with on-line hemodiafiltration, with "highflux" membranes over a period of 3-6 months, significantly reduces inflammation, oxidative stress and resistance to erythropoietin activity, compared to hemodialysis with "low-flux" membranes [17,18]. Hemodialysis membranes (vitamin E-coated hemodialysis) have also shown the reduction of lipid peroxidation parameters values in the serum, such as: malondialdehyde (MDA), thiobarbituric acid reactive substances (TBARS) and oxidized LDL cholesterol (oxLDL) [19][20][21][22][23][24]. Some studies highlighted that these membranes also reduce the concentration of oxidative nucleic acid parameters such as 8-OHdG (8-hydroxydeoxyguanosine) and the concentration of microinflammatory parameters (CRP, interleukin-6) [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly lower concentration of oxidative stress parameters is achieved on-line by hemodiafiltration with a vitamin E coated membrane in continuity over a 3-6 months period relative to standard hemodialysis with a low-flux membrane without vitamin E. The results of clinical trials suggest that healing with on-line hemodiafiltration, with "highflux" membranes over a period of 3-6 months, significantly reduces inflammation, oxidative stress and resistance to erythropoietin activity, compared to hemodialysis with "low-flux" membranes [17,18]. Hemodialysis membranes (vitamin E-coated hemodialysis) have also shown the reduction of lipid peroxidation parameters values in the serum, such as: malondialdehyde (MDA), thiobarbituric acid reactive substances (TBARS) and oxidized LDL cholesterol (oxLDL) [19][20][21][22][23][24]. Some studies highlighted that these membranes also reduce the concentration of oxidative nucleic acid parameters such as 8-OHdG (8-hydroxydeoxyguanosine) and the concentration of microinflammatory parameters (CRP, interleukin-6) [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodialysis membranes (vitamin E-coated hemodialysis) have also shown the reduction of lipid peroxidation parameters values in the serum, such as: malondialdehyde (MDA), thiobarbituric acid reactive substances (TBARS) and oxidized LDL cholesterol (oxLDL) [19][20][21][22][23][24]. Some studies highlighted that these membranes also reduce the concentration of oxidative nucleic acid parameters such as 8-OHdG (8-hydroxydeoxyguanosine) and the concentration of microinflammatory parameters (CRP, interleukin-6) [19][20][21][22][23][24]. Treatment with high-flux hemodialysis with polysulphonic membrane-bound vitamin E over a period of three to six months significantly reduces oxidative stress, microinflammation, erythropoietin resistance index, corrects the treatment of anemia, reduces the amount of erythropoietin and the thickness of intima-media of carotid arteries in population of patients treated with regular hemodialysis without affecting hemodialysis adequacy parameters (Kt/V index) [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further pointed out that the baseline ERI levels were higher in the studies describing ESA‐sparing effects of vitamin‐E‐coated membranes than in those showing no such effects . This notion holds true for a recent multicenter trial of a vitamin‐E‐coated membrane that reports an ESA‐sparing effect of the membrane in hemodialysis patients with median ERI of 12.8 . It appears that the ESA‐sparing potentials of the vitamin‐E‐coated membrane and the NV dialyzer are independent of their effects on systemic inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…Vitamin E coated dialyzers potentially may have an antioxidative effect, and small studies have suggested greater response to erythropoietins . However, these preliminary reports have not been substantiated to show more robust and sustained benefits.…”
Section: Dialyzer Specificationsmentioning
confidence: 98%